Design, implementation and evaluation of a long-term educational faculty development program for clinical faculty - Mahla Salajegheh (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: Faculty development programs by improving clinical faculty members' educational skills affect society's health. Despite all the efforts for the educational development of clinical faculty, these programs do not always have adequate efficiency because of some challenges. This study aimed to design, implement and evaluate a long-term educational faculty development program for clinical faculty members. Materials & Methods: This triangulation study was conducted from September 2021 to February 2022. The program designed by adopting Harden's 10 Questions of educational program development framework approach. Based on Sociocultural theory, a longitudinal, informal program performed in a group setting for eighty clinical faculty members. For program evaluation, a questionnaire based on the CIPP evaluation model was developed and tested psychometrically. Results: The results indicated the overall satisfaction with faculty development program was high. Participants reported awareness of strengths and weaknesses in education, more self-confidence, higher motivation in teaching, acquiring teaching skills in clinical settings, and providing effective feedback as the program's achievements. Conclusion: The combination of informal, longitudinal, and group-based approach increased the program's efficiency. This approach had short-term results such as enhancement of participants' educational skills, improvement in the process of clinical education, and training clinical educators for future faculty development programs. hopefully, it will increase organizational capacities in the long time.